2017
DOI: 10.1515/ace-2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Behaviour of Steel Tubular Columns for Varying in Filled Concrete

Abstract: This paper investigates the behaviour of axially-loaded tubular columns filled with M20 grade concrete and partially replaced concrete. The parameters varying in the study are slenderness ratio (13.27, 16.58 & 19.9), and normal M20 grade concrete, partially replaced quarry dust and concrete debris. The effects of the various concrete mixes and composite action between the steel tube and the concrete core are studied and a graph visualizing the differences between the load carrying capacity and the axial deflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Yang et al [23] analyzed that with the increase of substitution rate, the column bearing capacity decreases: European Standard EC4 bearing capacity calculation results are more in line with the test values; and based on the design formula of CFST, a simplified design formula for RACFST members under different conditions is proposed. Sangeetha et al [24] showed that increasing the length-to-finish ratio, the mechanical properties of RACFST columns decrease. Zhang Xianggang et al [25] showed that the ductility of square columns is less than that of circular columns, and the length to slenderness ratio has a greater effect on the bearing capacity of square section columns,In the calculation of bearing capacity and stiffness, the domestic codes are more in line with the test results.…”
Section: Mechanical Properties and Analysis Of Axial Compressionmentioning
confidence: 99%
“…Yang et al [23] analyzed that with the increase of substitution rate, the column bearing capacity decreases: European Standard EC4 bearing capacity calculation results are more in line with the test values; and based on the design formula of CFST, a simplified design formula for RACFST members under different conditions is proposed. Sangeetha et al [24] showed that increasing the length-to-finish ratio, the mechanical properties of RACFST columns decrease. Zhang Xianggang et al [25] showed that the ductility of square columns is less than that of circular columns, and the length to slenderness ratio has a greater effect on the bearing capacity of square section columns,In the calculation of bearing capacity and stiffness, the domestic codes are more in line with the test results.…”
Section: Mechanical Properties and Analysis Of Axial Compressionmentioning
confidence: 99%
“…Another study on steel-reinforced concrete-filled steel tubular (SRCFST) columns found that they exhibited high strength and fire resistance due to composite action enhancing cyclic performance, with circular cross-sections showing superior behaviour [57]. The composite action between steel tubular sections and concrete enhanced load-carrying capacity by 32%, with factors like slenderness ratio influencing strength and ductility indices in CFST columns [58]. However, these studies also pointed out that current design codes may not accurately predict the strength of these composite columns, indicating a need for code improvements to account for the composite action more effectively [7,12].…”
Section: Composite Actionmentioning
confidence: 99%
“…CFST structure is widely used in housing construction and bridge engineering [1][2][3]. However, the problem of core concrete and steel tube voiding (including debonding) has always been the research focus of scholars.…”
Section: Introductionmentioning
confidence: 99%